2022
DOI: 10.1088/1361-6528/ac87b6
|View full text |Cite
|
Sign up to set email alerts
|

Operando photoelectron spectroscopy analysis of graphene field-effect transistors

Abstract: In this study, operando photoelectron spectroscopy was used to characterize the performance of graphene field-effect transistors under working conditions. By sweeping the back-gate voltages, the carrier concentration of the graphene channel on the 150 nm Si3N4/Si substrate was tuned. From the C1s core level spectra acquired under the application of different gate voltages, the binding energy shifts caused by electric-field effects were obtained and analyzed. Together with the C1s peak shape information and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…The last but not the least, there has a study characterizing the performance of graphene FETs using an operando XPS under working conditions [22]. In the study, Lu et al could identified the presence of local potential across the x-ray beam spot associated with defects and gate leakage current.…”
mentioning
confidence: 99%
“…The last but not the least, there has a study characterizing the performance of graphene FETs using an operando XPS under working conditions [22]. In the study, Lu et al could identified the presence of local potential across the x-ray beam spot associated with defects and gate leakage current.…”
mentioning
confidence: 99%